2015
DOI: 10.18052/www.scipress.com/ilcpa.50.35
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Screening 6-Aryl-2-(Amino/Methoxy)-4-[(4′-Difluoro Methoxy) (3′-Hydroxy) Phenyl] Nicotinonitrile

Abstract: A series of an easy and efficient route for the synthesis of some new 2-amino-3-cyanopyridine (4a-4i) and 2-methoxy-3-cyanopyridine (5a-5i) derivatives were synthesized through the reaction of various chalcone (3a-3i) with malononitrile in presence of ammonium acetate and sodium methoxide, respectively. The constitutions of the all synthesized compounds have been established by the IR, 1H-NMR, Mass spectral data and Elemental analysis. Furthermore, all the synthesized products were screened for their antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Reaction mixture was refluxed at 60 °C for 8 hours, poured into crushed ice water, the product was extracted with 20 mL ethyl acetate. The organic layer was washed with brine, dry over sodium sulphate and evaporated under reduced pressure [29].…”
Section: Conventional Methodsmentioning
confidence: 99%
“…Reaction mixture was refluxed at 60 °C for 8 hours, poured into crushed ice water, the product was extracted with 20 mL ethyl acetate. The organic layer was washed with brine, dry over sodium sulphate and evaporated under reduced pressure [29].…”
Section: Conventional Methodsmentioning
confidence: 99%
“…made two series of 2‐aminonicotinonitriles 207a – i and 2‐methoxynicotinonitriles 208a – i from chalcones 206a – i by refluxing with ammonium formate and malononitrile in ethanol and/or sodium methoxide in ethanol for 8–12 h, respectively. The antimicrobial activity of 207a – i and 208a – i has been investigated and revealed that most of the tested compounds have moderate antibacterial activity with minimum inhibitory concentrations within 20 and 80 μg/mL and low antifungal activity (Scheme ) .…”
Section: Antimicrobial Activitymentioning
confidence: 99%